THE ANALYSIS OF COMPLIANCE DIRECTOR'S STRATEGY IN ACHIEVING FINANCIAL HEALTH OF BANK LEVEL AT PT. BPR KREDIT MANDIRI SULAWESI SELATAN SEJAHTERA - Oroh, Rivaldy; Anshar, Muh. Ashary; Suwandaru, Rachman (International Journal of Multidisciplinary Research and Literature, 2025)
This study was conducted to explore the strategies implemented by the Compliance Director in realising a good level of bank health at PT. BPR Kredit Mandiri Sulawesi Selatan Sejahtera. Regulators and other stakeholders are gravely concerned about the growing number of BPRs that are experiencing financial difficulties and even being liquidated. Bank health is a critical metric that demonstrates the economic stability and quality of performance. With the increasing complexity of regulations in the banking sector, the role of the Compliance Director becomes crucial in ensuring compliance with applicable laws and maintaining bank stability. The research approach employed is qualitative, with a phenomenological design, which involves in-depth interviews with informants from relevant parties, including the President, Director, Commissioners, and other bank officials, as well as an analysis of related documents. The results of the study indicate that the Compliance Director at PT. BPR Kredit Mandiri Sulawesi Selatan Sejahtera implements strategies that involve the implementation of good governance, effective risk management, and prudent management of profitability and capital factors. These strategies contribute to enhancing the bank's health, with a focus on regulatory oversight and strengthening internal policies and procedures. Additionally, periodic evaluations of policies and routine training for employees help strengthen the organisation's culture of compliance. The study's conclusion suggests that implementing policies that adhere to the principles of good corporate governance and effective risk management can help maintain the bank's stable finances and operations. This study helps us understand what the Compliance Director does to make the bank healthier. Further research is needed on how technology can be utilised to enhance compliance and risk management